Antipsychotic drugs elicit cytotoxicity in glioblastoma multiforme in a calcium‐dependent, non‐D2 receptor‐dependent, manner. Issue 3 (18th May 2021) - Weissenrieder, Jillian S.; Reed, Jessie L.; Moldovan, George‐Lucian; Johnson, Martin T.; Trebak, Mohamed; Neighbors, Jeffrey D.; Mailman, Richard B.; Hohl, Raymond J.
Abstract: Dopamine D2 ‐like receptor antagonists have been suggested as being potential anticancer therapeutics with specific utility for central nervous system cancers due to their ability to cross the blood‐brain barrier. Despite a plethora of data reporting anticancer effects for D2 R antagonists in cell or animal studies, the ligand concentrations or doses required to achieve such effects greatly exceed the levels known to cause high degrees of occupancy of the D2 receptor. To resolve this conundrum, we interrogated a panel of glioblastoma multiforme (GBM) cell lines using D2 antagonists of varying chemotype. We studied the cytotoxic effects of these compounds, and also ascertained the expression of D2 receptors (D2 R) on these cells. Although several chemotypes of D2 R antagonists, including phenothiazines and phenylbutylpiperidines, were effective against GBM cell line cultures, the highly selective antagonist remoxipride had no anticancer activity at biologically relevant concentrations. Moreover the D2 R antagonist‐induced cytotoxicity in monolayer cultures was independent of whether the cells expressed D2 R. Instead, cytotoxicity was associated with a rapid, high‐magnitude calcium flux into the cytoplasm and mitochondria, which then induced depolarization and apoptosis. Blocking this flux protected the GBM cell lines U87MG, U251MG, and A172. Together, these data suggest that the cytotoxicity of these D2 R antagonists involves calcium signaling mechanisms, not D2 R antagonism. Repurposing of existing drugs should focus on the former, not latter, mechanism. Abstract : D2 R antagonists show cytotoxic effects of varying degree in numerous glioblastoma cell lines, indicating potential for use as anticancer agents in brain cancers.